Foreign language anxiety in EFL classrooms: teachers' perceptions, challenges, and strategies for mitigation - Attia, Shaden; Algazo, Muath (Frontiers in Education, 2025)
This study investigates Foreign Language Anxiety (FLA) in English as a foreign language (EFL) classrooms in Egyptian higher education. The study was conducted at multiple universities in Egypt, where English is widely taught and learned as a foreign language. Data was collected through a questionnaire completed by 49 EFL instructors, supplemented by five one-to-one semi-structured interviews with participants from the questionnaire. The results demonstrate that EFL teachers generally acknowledge and frequently observe FLA among students, particularly during speaking activities. Specific sub-skills such as summarizing and presenting were identified as anxiety-inducing. Although some instructors consider FLA motivating, others view it as detrimental to student progress. Instructors also suggest creating supportive environments where mistakes are valued as part of the learning process to mitigate FLA. Interestingly, it was found that instructors themselves may experience FLA, particularly when speaking with native speakers or teaching in a second language (L2). Strategies suggested by instructors to alleviate FLA include group discussions, role plays, individual activities with preparation, and peer support. Overall, instructors' attitudes, rapport, and feedback play a crucial role in managing FLA levels in the classroom. This study contributes to raising awareness among stakeholders toward FLA in Egypt and the broader EFL context.